Implementasi Encapsulation Jaringan Redudansi VLAN Menggunakan Metode Hot Standby Router Protocol (HSRP) - Hendy Dwi Haryoyudhanto; Iskandar Fitri; Andri Aningsih (JOINTECS (Journal of Information Technology and Computer Science), 2020)
Local Area Network is currently often used to minimize a public work, different network segmentation in a building requires attention in designing a network that has dense traffic and often occurs down and vails over on a network flow, certainly requires performance optimal and efficient network, by way of network encapsulation with one channel and dividing each network segmentation by VLAN. The purpose of this paper is to apply a design by optimizing a network using the network redundancy method to create a more optimal network. This redundancy method is a method that moves a network path when downtime occurs on one of the routers that are automatically changed to an active router and a standby router. In the implementation of the design using GNS3 software to create network topology and design. With the results of tests that have been carried out using the simulator, packet loss from using the HSRP method is at VLAN10 0.11%, VLAN20 0.13%, VLAN30 0.30%, VLAN40 0.13%, VLAN50 0.22% AND VLAN60 0.16%. So the purpose of research makes a network more optimal and flexible